Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) untuk Meningkatkan Hasil Belajar: Penerapan Model Pembelajaran Kooperatif Tipe Group Investigation (GI) untuk Meningkatkan Hasil Belajar - Susila, Gede Darma Gita; Satyawan, I Made; Wijaya, Made Agus (Jurnal IKA, 2024)
This study aims to determine the increase in learning activities and learning outcomes of passing control techniques (inside foot) in football through the application of the GI type cooperative learning model. This study is a classroom action research with the subjects of the study being all students of class VIII 1 SMP Negeri 2 Singaraja in the 2023/2024 academic year totaling 22 students. The data analysis method uses descriptive statistical analysis. The results of the study showed that at the initial observation stage, student learning success for learning activities was only 77.00%. In the implementation of cycle I, there was an increase in student learning outcomes of 81.6%. The implementation of cycle II actions also saw an increase in success to 90.9% of students meeting the minimum completeness criteria. Then, student learning success for learning outcomes was only 18.20%. In the implementation of cycle I, there was an increase in student learning outcomes of 81.8%. The implementation of cycle II actions also saw an increase in success to 92.4% of students meeting the minimum completeness criteria. Based on the results of classical learning, it can be concluded that the GI type cooperative learning model can improve learning activities and learning outcomes of passing control techniques (inside foot) in football for students of class VIII 1 of SMP Negeri 2 Singaraja. It is recommended that PJOK teachers can improve the GI type cooperative learning model on the material of passing control techniques (inside foot) in football for students of class VIII 1 of SMP Negeri 2 Singaraja because through this study it has been proven to improve learning activities and learning outcomes.